Impact of the merger decision of Islamic bank on Islamic capital market reaction in Indonesia - Saputra, Moch. Adika; Wulandari, Santi; Muttaqin, Ibnu (Journal of Islamic Economics Management and Business (JIEMB), 2022)
One way to strengthen the banking industry is to expand externally through mergers. The expected impact on the capital market due to the merger is a positive change in price fluctuations and trading volume of shares on the market, in which the merger makes banking performance more developed. This study aims to determine the reaction of the Indonesian Islamic capital market to the decision to merge Islamic banks owned by state-owned enterprises in Indonesia, namely Bank Syariah Indonesia, which is a bank resulting from a merger between PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah. This type of research includes quantitative research and an independent t-test as a statistical approach to comparative analysis. The results of the study show that there is a positive reaction from the capital market to the decision to merge state-owned Islamic banks. This can be seen from price activity, trading volume and stock returns. This research can provide an overview of the market reaction to an event